2019
DOI: 10.5830/cvja-2018-054
|View full text |Cite
|
Sign up to set email alerts
|

Management of low-density lipoprotein cholesterol levels in South Africa: the International ChoLesterol management Practice Study (ICLPS)

Abstract: The International Cholesterol Management Practice Study (ICLPS) South Africa investigated achievement of European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guideline low-density lipoprotein cholesterol (LDL-C) targets in real-world clinical practice. Demographic data, clinical characteristics, cardiovascular risk factors, lipidmodifying medications, lipid values and investigator's assessment of cardiovascular risk were recorded for 396 patients on stable lipid-modifying therapy. Most (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
4
9
0
Order By: Relevance
“…In one multi-centre study of over 7 000 participants in Europe, only 45 % of the participants with atherogenic dyslipidaemia were on lipid-lowering therapy [ 20 ]. In another SA study that evaluated the achievement of LDL-C targets in patients on lipid-lowering therapy in clinical practice, only 41.4 % of patients achieved their LDL-C target [ 21 ]. In the European study, approximately 27 % [ 20 ] and in the SA study 64 % [ 21 ] of the participants had T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one multi-centre study of over 7 000 participants in Europe, only 45 % of the participants with atherogenic dyslipidaemia were on lipid-lowering therapy [ 20 ]. In another SA study that evaluated the achievement of LDL-C targets in patients on lipid-lowering therapy in clinical practice, only 41.4 % of patients achieved their LDL-C target [ 21 ]. In the European study, approximately 27 % [ 20 ] and in the SA study 64 % [ 21 ] of the participants had T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In another SA study that evaluated the achievement of LDL-C targets in patients on lipid-lowering therapy in clinical practice, only 41.4 % of patients achieved their LDL-C target [ 21 ]. In the European study, approximately 27 % [ 20 ] and in the SA study 64 % [ 21 ] of the participants had T2DM. A previous report assessing lipid goal attainment in patients on lipid-lowering therapy in central SA was done in the private sector and included patients with and without DM [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the South African context, the prevalence of uncontrolled dyslipidaemia is reflected in studies done in the private sector only, 20 and in both the public and private sectors. 21,22 In these studies, the prevalence of uncontrolled LDL-C ranged from 47.7% to 58.6%.…”
Section: Discussionmentioning
confidence: 97%
“…Concerns for safety, toxicity and side effects, as well as ethnicity and lower socio-economic status, have been cited as patient factors for poor statin adherence. [20][21][22] In the public sector the lack of drug availability, due to formulary restrictions and at times stock shortage, is a common problem while staff shortage in large diabetic clinics impairs the holistic management of diabetic dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, significant gaps were found between guideline recommendations and real-world clinical practice. Previous studies also reported significant gaps between evidence-based medicine and real-world clinical practice (18)(19)(20)(21) lower than those in the Get-With-The-Guidelines-Stroke Registry several years ago with 51.3% for <2.6 mmol/L and 19.8% for <1.8 mmol/L (18). Encouragingly, however, temporal trend analysis showed there is an increasing trend for the attainment rates of LDL-C <2.6 mmol/L, LDL-C <1.8 mmol/L, LDL-C <1.4 mmol/L and prescription of cholesterol-lowering agents at discharge, though the increase was only marginal.…”
Section: Discussionmentioning
confidence: 99%